2017
DOI: 10.3390/catal7090265
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of Lignin-Derived Phenols: From Fundamental Studies towards Industrial Applications

Abstract: Hydrodeoxygenation (HDO) of bio-oils, lignin and their model compounds is summarized in this review. The main emphasis is put on elucidating the reaction network, catalyst stability and time-on-stream behavior, in order to better understand the prerequisite for industrial utilization of biomass in HDO to produce fuels and chemicals. The results have shown that more oxygenated feedstock, selection of temperature and pressure as well as presence of certain catalyst poisons or co-feed have a prominent role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 84 publications
(363 reference statements)
2
60
0
Order By: Relevance
“…Initially absent of toluene, the 2-step upgraded oil was composed of 0.017 g of toluene. It was previously reported that it is among the plausible products of guaiacol conversion [62,63], in agreement with the lower guaiacol concentration in the upgraded products in comparison to the feed. The concentration of benzene also increased in the UOP 2 nd ,Ni-Cr,325 • C from 0.006 g to 0.0181 g. Another six compounds belonging to the benzene group were observed in the 2-step upgraded oil with 1-methyl-naphtalene, the heterocyclic aromatic compound with the highest concentration (0.038 g), as evidence of aromatic condensation taking place.…”
Section: Characterization Of Upgraded Liquid Products and Feedstocks supporting
confidence: 82%
“…Initially absent of toluene, the 2-step upgraded oil was composed of 0.017 g of toluene. It was previously reported that it is among the plausible products of guaiacol conversion [62,63], in agreement with the lower guaiacol concentration in the upgraded products in comparison to the feed. The concentration of benzene also increased in the UOP 2 nd ,Ni-Cr,325 • C from 0.006 g to 0.0181 g. Another six compounds belonging to the benzene group were observed in the 2-step upgraded oil with 1-methyl-naphtalene, the heterocyclic aromatic compound with the highest concentration (0.038 g), as evidence of aromatic condensation taking place.…”
Section: Characterization Of Upgraded Liquid Products and Feedstocks supporting
confidence: 82%
“…The latter is undesirable as alkanes are less valuable than aromatics and typically only have fuel value. In addition, methoxy removal by hydrogenolysis reactions may also occur, as shown by model component studies, 58,59 leading to the formation of methanol. The latter is likely not inert under the prevailing reaction conditions and may be converted to gas-phase components.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Hydrogenation and hydrodeoxygenation (HDO) of bio-oils is currently a significant research undertaking [1,2] and a wide range of conditions and catalysts have been investigated [3]. In this paper we will report on the liquid-phase hydrogenation and HDO of anisole, phenol and 4-methoxyphenol.…”
Section: Introductionmentioning
confidence: 99%